Individual and contextual factors associated to the self-perception of oral health in Brazilian adults - Janmille Valdivino da Silva; Angelo Giuseppe Roncalli da Costa Oliveira (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To analyze how individual characteristics and the social context, together, are associated with self-perception of the oral health. METHODS A multilevel cross-sectional study with data from the Brazilian National Health Survey 2013, the United Nations Development Program, and the National Registry of Health Establishments. The explanatory variables for the "oral health perception" outcome were grouped, according to the study framework, into biological characteristics (sex, color, age), proximal social determinants (literacy, household crowding, and socioeconomic stratification), and distal (years of schooling expectancy at age 18, GINI, Human Development Index, and per capita income). The described analysis was performed, along with bivariate Poisson analysis and multilevel Poisson analysis for the construction of the explanatory model of oral health perception. All analyzes considered the sample weights. RESULTS Both the biological characteristics and the proximal and distal social determinants were associated with the perception of oral health in the bivariate analysis. A higher prevalence of bad oral health was associated to lower years of schooling expectancy (PR = 1.31), lower per capita income (PR = 1.45), higher income concentration (PR = 1.41), and worse human development (PR = 1.45). Inversely, oral health services in both primary and secondary care were negatively associated with oral health perception. All the biological and individual social characteristics, except reading and writing, made up the final explanatory model along with the distal social determinants of the Human Development Index and coverage of basic care in the multilevel analysis. CONCLUSIONS Biological factors, individual and contextual social determinants were associate synergistically with the population's perception of oral health. It is necessary to improve individual living conditions and the implementation of public social policies to improve the oral health of the population.